After the rain - Jennings, John, 1970- (Abrams ComicArts - Megascope, 2021)
After the Rain is a graphic novel adaptation of Nnedi Okorafor's short story "On the Road." The drama takes place in a small Nigerian town during a violent and unexpected storm. A Nigerian-American woman named Chioma answers a knock at her door and is horrified to see a boy with a severe head wound standing at her doorstep. He reaches for her, and his touch burns like fire. Something is very wrong. Haunted and hunted, Chioma must embrace her heritage in order to survive. John Jennings and David Brame's graphic novel collaboration uses bold art and colors to powerfully tell this tale of identity and destiny.